Does Okun's law suffer from COVID-19? Evidence from Europe and the US - A research note - Jan Russnak; Georg Stadtmann; Lilli Zimmermann (European University Viadrina, Department of Business Administration and Economics, 2023)
We analyse the effect of COVID-19 on the Okun's law relationship for several EU countries and the US. Results are based on regressions and a systematic DF-Beta analysis. Our results indicate that the year 2020 is an outlier in the Okun relationship. However, the direction of change is different in the European countries compared to the US.
urn:nbn:de:kobv:521-opus4-12945
Keywords: E30; J60; 330; Okun's law; Covid-19; Outliers